(untitled) (Malay Literature, 2017)
The piece investigated in this article, entitled Cetra Empat Orang Fakir (The Tale of the Four Dervishes) and preserved in the unique manuscript Q 11.4A/27 in the National Library of Singapore, allows us to reconsider. It was translated in 1846 and, despite the claim of the translator, cannot be traced to a Persian original. In fact, it is a rendition of Bagh-o-bahar (Garden and Spring, 1802) by the outstanding Urdu writer Mir Amman. Thus, The Tale of the Four Dervishes is the first Malay translation of an Urdu romance. This article investigates information about the translator of Bagh-o-bahar, a Jawi Peranakan named Mahmud bin Sayid Mu’alim, and his socio-cultural environment. It also provides the reader with the content of the Cetra and discusses the strategies of translation used by Mahmud and a combination of old and new features in his work. Even if not without caveats, the findings of this article can also be extrapolated to the lesser-documented literary pieces of the first wave of Islamicate India’s influence. Keywords: Islamicate India, traditional Malay literature, Persian, Urdu, Mir Amman, Bagh-o-bahar, The Tale of the Four Dervishes (TFD), Jawi Peranakan, Mahmud bin Sayid Mu’alim, translation strategies